The Jewish economic elite : making modern Europe - Aust, Cornelia (German Jewish cultures., 2018)
"In this rich transnational history, Cornelia Aust traces Jewish Ashkenazi families as they moved across Europe and established new commercial and entrepreneurial networks as they went. Aust balances economic history with elaborate discussions of Jewish marriage patterns, women's economic activity, and intimate family life. Following their travels from Amsterdam to Warsaw, Aust opens a multifaceted window into the lives, relationships, and changing conditions of Jewish economic activity of a new Jewish mercantile elite"--